DESCRIPTION OF STUDENTS' SPIRITUAL INTELLIGENCE IN ISLAMIC EDUCATION SUBJECTS - Muzakkir, Muzakkir; Hidayat, Wahyu; Hamsiah, Hamsiah; Lathifu, Sunni (STAI Tuanku Tambusai, 2022)
ABSTRACTSpiritual intelligence helps a person to find meaning in life and happiness. A person's intelligence can be shown in his daily behavior. This study aims to identify the description of students' spiritual intelligence. The method used in this research is a qualitative method with a case study approach at SMP Negeri 3 Parepare. Data collection techniques used in this study through interviews, observation, and documentation. The main instrument in qualitative research is the researcher himself. The step is to examine all existing data, and then researchers can draw certain conclusions from the results of their understanding based on the communication process approach so that the data is saturated. The results show that students have the ability to adapt to the environment, both at school and at home, as well as they really value time, every task given by their teacher, always completes it on time, they also respect the opinions of others. Have a spirit of awareness for the importance of reading the Qur'an. Participate in helping and participating in the success of learning to read the Qur'an with recitation songs in extracurricular Islamic spiritual development so that good relationships and cooperation are established between students and the surrounding community. have an independent nature because they have a good habit of praying Duha without being asked by their PAI teacher and getting up to pray at dawn without being woken up by their parents.